Immune response mechanisms in acute and chronic pancreatitis: strategies for therapeutic intervention - Glaubitz, Juliane; Asgarbeik, Saeedeh; Lange, Rabea; Mazloum, Hala; Elsheikh, Hager; Weiss, Frank Ulrich; Sendler, Matthias (Frontiers in Immunology, 2023)
Acute pancreatitis (AP) is one of the most common inflammatory diseases of the gastrointestinal tract and a steady rising diagnosis for inpatient hospitalization. About one in four patients, who experience an episode of AP, will develop chronic pancreatitis (CP) over time. While the initiating causes of pancreatitis can be complex, they consistently elicit an immune response that significantly determines the severity and course of the disease. Overall, AP is associated with a significant mortality rate of 1-5%, which is caused by either an excessive pro-inflammation, or a strong compensatory inhibition of bacterial defense mechanisms which lead to a severe necrotizing form of pancreatitis. At the time-point of hospitalization the already initiated immune response is the only promising common therapeutic target to treat or prevent a severe disease course. However, the complexity of the immune response requires fine-balanced therapeutic intervention which in addition is limited by the fact that a significant proportion of patients is in danger of development or progress to recurrent and chronic disease. Based on the recent literature we survey the disease-relevant immune mechanisms and evaluate appropriate and promising therapeutic targets for the treatment of acute and chronic pancreatitis.